BLOOD LIPID AND NON-LIPID BIOMARKERS IN NOVOSIBIRSK MEN WITH CORONARY ATHEROSCLEROSIS - Yu. I. Ragino; A. M. Chernyavsky; A. V. Tikhonov; S. Yu. Tsymbal; Ya. V. Polonskaya; E. V. Semaeva; M. V. Ivanova; M. I. Voevoda (Российский кардиологический журнал, 2009)
Blood lipid (total cholesterol (CH), triglycerides, low and high-density lipoprotein CH (LDL-CH, HDL-CH), lipoprotein (a)) and non-lipid (high-sensitive C-reactive protein (hsCRP), homocysteine, interleukins (IL) beta, 6, and 8, tumor necrosis factor (TNF), metalloproteinase (MP) 3 and 9) were measured in 96 Novosibirsk men, aged 42–70 years, with angiography-confirmed coronary atherosclerosis and Functional Class II-IV stable effort angina, but without acute coronary syndrome. More than 70% of the patients demonstrated an increase in blood levels of total CH, LDL-CH, hsCRP, homocysteine, IL-6, IL-8, and especially MP-9 (elevated in 100% of the men examined).